2014
DOI: 10.4025/actascitechnol.v36i3.18561
|View full text |Cite
|
Sign up to set email alerts
|

<b>Preparation of a cereal bar containing bocaiuva: physical, nutritional, microbiological and sensory evaluation

Abstract: ABSTRACT. Regional fruit have been increasingly used in recent years in the preparation of foodstuffs because besides promoting the biome preservation, it is obtained differentiated and value-added products. This study aimed to prepare cereal bars containing pulp and kernel of bocaiuva and determine the nutritional quality, assess the acceptability, and microbiological quality. Two formulations of cereal bar were prepared with pulp dehydrated by osmoconvection and kernel of bocaiuva. The formulations were anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 22 publications
2
7
0
Order By: Relevance
“…The Maillard reaction may occur during thermal processing and/or long-term storage of foods containing protein and reducing sugar [31]. Compared to other studies, the protein content of the food bar was similar to that found by da Silva et al [3], for cereal bars with marolo flour, ranging from 6.12 to 7.25 g⋅100 g −1 and Munhoz et al [29], for cereal bars with bocaiuva, ranging from 7.69 to 8.33 g⋅100 g −1 . The different formulations and the 6-month storage do not significantly interfere with the dietary fiber content of food bars.…”
Section: Resultssupporting
confidence: 48%
See 1 more Smart Citation
“…The Maillard reaction may occur during thermal processing and/or long-term storage of foods containing protein and reducing sugar [31]. Compared to other studies, the protein content of the food bar was similar to that found by da Silva et al [3], for cereal bars with marolo flour, ranging from 6.12 to 7.25 g⋅100 g −1 and Munhoz et al [29], for cereal bars with bocaiuva, ranging from 7.69 to 8.33 g⋅100 g −1 . The different formulations and the 6-month storage do not significantly interfere with the dietary fiber content of food bars.…”
Section: Resultssupporting
confidence: 48%
“…Munhoz et al [29] studied cereal bars with bocaiuva and found higher lipid content, which ranged from 12.31 to 13.55 g⋅100 g −1 . da Silva et al [3] also studied marolo pulp flour cereal bars and found lower values for the lipid content, ranging from 2.12 to 2.6 g⋅100 g −1 .…”
Section: Resultsmentioning
confidence: 99%
“…The calcium content in the formulated snack bar and control bar was 226.89 mg and 172.58 mg. These results correlated with Munhoz et al ( 2014 ) findings that observed a gradual increase in mineral content with increasing concentration of bocaiuva in the cereal snack bar.…”
Section: Resultssupporting
confidence: 91%
“…BFB acceptance was evaluated in 3 preparations (Table 5). Soup was the most accepted, and as reported by the testers, its flavor was the main reason for purchasing and consuming the product (Lima et al, 2010;Barbosa & Coelho, 2008;Munhoz et al, 2014). The acceptability index (AI) for BPBbased soup was 75%, indicating high marketing potential.…”
Section: Sensory Analysismentioning
confidence: 95%